Is there a cranial nerve other than the 7th co- involved in bell’s palsy? Answer to the systematic review - Razif Abas; Aspalilah A; Mohd Amir K; Wong, KH; Siti Nurma Hanim H; Choy, KW; Nor Farid MN; Muhammad Hibatullah R (Pusat Perubatan Universiti Kebangsaan Malaysia, 2022)
Bell’s palsy is characterised by one-sided lower motor neuron impairment of the facial nerve. Even though Bell’s palsy is a peripheral facial nerve palsy, other cranial nerves should be investigated, because they are anatomically interconnected rather than isolated. The study aimed to look for evidence of other cranial nerves being involved in Bell’s palsy. CINAHL, Academic Search Complete, MEDLINE, SPORTDiscus, and Scopus, all of which were updated until May 2021, were used to conduct a comprehensive search. Bell’s palsy research focused on the origins and cause of the condition, regardless of study design, was eligible for inclusion. Animal research, non-English studies, grey literature, studies with no full text available, and those published in non-peer-reviewed journals, were excluded. While 3883 papers were found during the initial search, only 13 were included in the final study. The Joanna Briggs Institute Manual for Evidence Synthesis and Sackett’s standard of evidence was used to assess the validity of the papers that were screened. The most common type was case series (n=5), followed by case-control (n=4), case report (n=3), and cross-sectional (n=1). Most of the articles were categorised as Level-IV (n=8), followed by Level-V (n=3), with only two studies classified as Level- III (n=2) by Sackett’s criteria. The trigeminal and vestibulocochlear nerves are the most involved cranial nerves in Bell’s palsy. The optic, oculomotor, trigeminal, vestibulocochlear, glossopharyngeal, vagus, and hypoglossal nerves are the seven cranial nerves potentially associated with Bell’s palsy.